Representation of Women in Novels by Dick and Felix Francis - Svobodová, Klára (Univerzita Pardubice, 2020)
The thesis is focused on analyzing women´s characters and their social roles in novels by Dick and his son Felix Francis. The aim is to compare roles of women in novels written by Dick Francis himself with novels which were written either by both authors together of solely by Felix Francis. This thesis questions whether the changes could be caused by the influence of Felix Francis who is representative of younger generation of writers growing up at the end of the second wave feminism and whose writing style is influenced by the popular culture of postfemnism.
Zobrazení žen v románech Dicka a Felixe Francisových
Keywords: angel in the house; feminism; gold digger; girl power; glass ceiling; career-women; patriarchal society; anděl v domě; feminismus; zlatokopka; holčičí síla; skleněný strop; kariéristka; patriarchální společnost